INTERPRETATION OF MERCURY INJECTION EXPERIMENTS USING A MINIMUM SET OF POROUS DESCRIPTORS DERIVED BY QUANTITATIVE IMAGE ANALYSIS - Anguy, Yannick; Belin, Sophie; Ehrlich, Robert; Ahmadi, Azita (Image Analysis and Stereology, 2011)
The porosity exposed in a series of petrographic thin sections from a sub-arkosic sandstone reservoir of the Alwyn area (North Sea) is described by 5 morphological porous descriptors, Pore-Types, obtained by quantitative image analysis procedures and pattern recognition algorithms developed by Ehrlich et al. (1991a). By combining Pore-Type data with capillary pressure curves, we obtain preliminary results showing that in the studied reservoir, the achieved Pore-Types relate better to petrophysics when they are complemented with a sedimentological information.